The evolutionary foundations of economics - Dopfer, Kurt (Cambridge University Press, 2005)
This volume brings together fifteen original articles from eminent economic scholars in their common efforts to reconstruct economics as an evolutionary science. Using meso economics as an analytical entity, bridging micro and macro economics as well as static and dynamic realms, a unified economic theory emerges.
Keywords: Evolutionary economics.; Economics.; Economics; Théorie de l'évolution économique.; Économie politique.; economics.; BUSINESS & ECONOMICS -- Economics -- Theory.; Evolutionary economics; Evolutorische Wirtschaft; Sociale evolutie.; Institutionele economie.; Économie évolutionniste.